Pengaruh Variasi Aktivator KOH dan NaCl terhadap Kapasitas Adsorpsi Biji Kapuk (Ceiba pentandra) dalam Penjerapan Ion Fe(II) - Kelvin Hadinatan; Iriany; Taslim; Okta Bani; Yesi Artanti; Nafis Ijlal Syach (Talenta Publisher (Universitas Sumatera Utara), 2026)
Heavy metal contamination such as iron (Fe) in wastewater is a significant environmental issue due to its negative impact on ecosystems and human health. This study aims to synthesize adsorbents from kapok seeds (Ceiba pentandra) by examining the effect of activator type (KOH and NaCl) and particle size (100 and 120 mesh) on the adsorption capacity of Fe(II) ions. The research methodology includes carbonation and chemical activation processes, followed by adsorption kinetics testing. The results showed that the use of NaCl activator with a particle size of 120 mesh provided the best performance with an equilibrium adsorption capacity of 89.75% and an iodine number of 127 mg/g. Kinetic analysis showed that the Fe(II) ion adsorption process followed a pseudo-second-order kinetic model with an R2 value of 0.999, indicating that the main adsorption mechanism was chemisorption through a two-step interaction involving diffusion and intermolecular interactions in the adsorbent area.